Orthogonal cutting of Wire and Arc Additive Manufactured parts - Fonseca, Pedro P. (2022)
project CARAVELA (POCI-01–0247-FEDER-039796) under the Competitiveness and Internationalization Operational Program, Regional Operational Program for Lisbon FEDER and Portugal 2020. Authors would like to extend their thanks the Portuguese Military Academy Research Center (CINAMIL) for the support provided to high-speed image acquisition. Publisher Copyright: © 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.